(untitled) (Carte Romanze, 2022)
In this article we examine an excerpt from the Berlin version of the Franco-Italian chanson de geste of Huon d’Auvergne in which a character named Zenat is mentioned. This hitherto unnoticed reference allows to call into question the problem of the authorship of Huon d’Auvergne, to reconnect the Huon to the Gui de Nanteuil of the Marciana Library in Venice and possibly to identify Zenat with the Giovanni Vigentino mentioned by Andrea da Barberino in his Storia di Ugone d’Avernia.